O ensino funcional dos conectivos condicionais nos anos finais do fundamental - Oliveira, José Rogério Viana de (2021)
More recent data from the Index of Development of Basic Education (Ideb), referring to 2019, place Fortaleza in second place among the capitals of the Northeast in performance. Despite this, with regard to learning Portuguese in the final years of elementary school, the average proficiency of students was 262.28, which corresponds to level 3 on the SAEB scale for the 9th grade, with 8 being the highest level on the scale. In order to identify the main difficulties related to the Portuguese language that justify this data, the results of the Diagnostic Assessments (ADR) of Fortaleza were analyzed: assessments prepared according to the SPAECE reference matrix and formed by a set of descriptors that demonstrate the skills expected at different stages of schooling. The indexes of correct answers by descriptors and the characteristics of the items of the three ADRs applied in 2019 to four 9th grade classes of a municipal school in Fortaleza were evaluated. The analysis showed that respondents had greater difficulty in the skill corresponding to descriptor 17, “recognizing the meaning of logical-discursive relationships marked by conjunctions, adverbs, etc.”, since 64.7% missed the corresponding questions. These results highlight the need for a pedagogical intervention aimed at improving the teaching-learning process of connectives, which can be done based on linguistic functionalism, which sees grammar in its relationship with the text, and in the three axes of teaching grammar, proposed by Vieira (2017): Axis 1, systematicity, which covers metalinguistic and epilinguistic activities; Axis 2, of functionality, which is related to the production of meaning, and Axis 3, of linguistic variation, which includes normative activities. Based on these assumptions, the activities of textbooks from the 8th and 9th grade of two collections adopted in public schools in Fortaleza were analyzed in order to verify, in this main pedagogical resource, the treatment given to the teaching of connectives in general, and, in particular, to the teaching of the conditional connectives, that are selected by the semantic abundance attested in the linguistic literature and by the recurrent use in genres consumed by young people. The results showed that: (1) the connectives are predominantly explored in metalinguistic activities; (2) there is little exploitation of conditional connectives ― of the total of 381 activities related to connectives, only 3.9% cover conditionals; (3) most activities regarding conditionals require only identification and classification of the connectives and clauses; (4) the use of grammar and its relationship to text is little or superficially explored; (5) linguistic variation, which is low in activities in general, is not explored in the approach to conditional connectives. In view of these results, a pedagogical proposal was elaborated, consisting of five workshops, aimed at the teacher, to be applied to 9th grade students, in order to lead students to recognize the meanings of conditional connectives and to use them properly in varied texts. Thus, it is expected to contribute to language teaching associated with practices recommended by official documents, which can develop students' communicative competence, in order to make them more apt to fully exercise their citizenship.